Sensitization, energy transfer and infra-red emission decay modulation in Yb3+-doped NaYF4 nanoparticles with visible light through a perfluoroanthraquinone chromophore - Haizhou Lu (Nature Portfolio, 2017)
Abstract Infra-red emission (980 nm) of sub 10 nm Yb3+-doped NaYF4 nanoparticles has been sensitized through the excitation of 2-hydroxyperfluoroanthraquinone chromophore (1,2,3,4,5,6,7-heptafluro-8-hydroxyanthracene-9,10-dione) functionalizing the nanoparticle surface. The sensitization is achieved with a broad range of visible light excitation (400–600 nm). The overall near infra-red (NIR) emission intensity of Yb3+ ions is increased by a factor 300 as a result of the broad and strong absorption of the chromophore compared with ytterbium’s intrinsic absorption. Besides the Yb3+ NIR emission, the hybrid composite shows organic chromophore-based visible emission in the orange-red region of the spectrum. We observe the energy migration process from the sensitized Yb3+ ions at the surface to those in the core of the particle using time-resolved optical spectroscopy. This highlights that the local environments for emitting Yb3+ ions at the surface and center of the nanoparticle are not identical, which causes important differences in the NIR emission dynamics. Based on the understanding of these processes, we suggest a simple strategy to control and modulate the decay time of the functionalized Yb3+-doped nanoparticles over a relatively large range by changing physical or chemical parameters in this model system.